Optimization of operating parameters on the recovery of copper ions from vetiver grass [Chrysopogon zizanioides (L.) Roberty] biomass by leaching process - Aragua, Richelle A.; Resurreccion, Augustus C. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The mobility and solubility of heavy metal to the environment pose harmful effects to human health, plants and animals. Phytoextraction is a promising technology which uses plants to clean up heavy metal contaminated environment. The direct disposal, however, of the harvested plant biomass from this approach could lead to secondary pollution for it is rich in extracted toxic metals that could eventually reach to the bodies of water and soil. In this study, the potential of the recovery of Cu ions through leaching process from Vetiver grass biomass was evaluated. Face-centered central composite design with four independent factors at three coded levels was used to examine and optimize the following operating parameters: temperature, stirring speed, reaction time, liquid/solid ratio, and the leaching kinetics was determined using shrinking core model. The results showed that 97 percent of Cu ions was leached using citric acid monohydrate at 70°C temperature, 32.18 mL/g solid-liquid ratio, 130 min. reaction time and 38 rpm stirring speed. From the ANOVA results, only temperature and liquid/solid ratio exhibit significant effects (p-values<0.5) on the overall leaching process of Cu ions from Vetiver grass biomass, while stirring speed and reaction time were not significant within the given range of coded values. In addition, it was found that the leaching kinetics was controlled by both interface transfer and product layer diffusion reaction. The calculated activation energy for the recovery of Cu ions is 32.14 kJ/mole in the reaction temperature span of 30°C to 70°
Thesis (Master of Science in Environmental Engineering)--University of the Philippines Diliman
Keywords: Coppe; Leachin; Phytoremediatio; Vetive